Status of MDR and Plasmid Profiling of ESBL producing E. coli and Klebsiella spp. isolated from milk of Bovine in Gangetic Plain Zone of Uttar Pradesh - Yadav, Vibha; Joshi, Rajesh Kumar; Joshi, Namita; Singh, Satyvart; Maurya, Satyendra Kumar; Srivastava, Dharam Prakash; Gupta, Rakesh Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Nowadays resistance to antibiotics of β-lactam groups is expanding rapidly and is one of the latest challenges faced by scientific community due to therapeutic failure. In the present study total 180 milk samples were collected from two district of Gangetic Plain Zone of Uttar Pradesh (India). Total 65 (36.11%) isolates were confirmed comprising 44 (24.4%) E. coli and 21 (11.67%) Klebsiella spp. by PCR analysis using uidA gene and 16S rRNA gene respectively, 35/180 (19.44%) isolates were confirmed as ESBL producers, constituting 12 (6.67%) E. coli and 23 (12.8%) Klebsiella spp. All ESBL positive isolates were subjected to antimicrobial resistance pattern using 17 antibiotics of 10 different classes. In this study all the isolates of E. coli and Klebsiella spp. were found 100% resistant to cefotaxime, cefpodoxime, ceftriazone and ampicillin. Both the isolates of E. coli and Klebsiella spp. revealed different susceptibility pattern to different non-β-lactam antibiotics except aminoglycosides class of antibiotics for which both the isolates were found 100% sensitive. The multi-drug resistance pattern was assessed by using MAR index. Out of total ESBL producers, 80.0% isolates were found MDR with 78.0% E. coli and 83.0% Klebsiella spp. Overall 12 resistance pattern were observed for E. coli ranging from 5 to 12 antibiotics and 09 for Klebsiella spp. ranging from 5 to 14 antibiotics. Plasmid profiling revealed total 71.42% isolates carrying plasmids with average molecular weight ranged between 1.0 Kb to > 10 Kb and number1-4.